Domain Unknown Function DUF1668-Containing Genes in Multiple Lineages Are Responsible for F1 Pollen Sterility in Rice - Sakata, Mitsukazu; Takano-Kai, Noriko; Miyazaki, Yuta; Kanamori, Hiroyuki; Wu, Jianzhong; Matsumoto, Takashi; Doi, Kazuyuki; Yasui, Hideshi; Yoshimura, Atsushi; Yamagata, Yoshiyuki (Frontiers in Plant Science, 2021)
Postzygotic reproductive isolation maintains species integrity and uniformity, and contributes to speciation by restricting the free gene flow between divergent species. In this study we identifiy causal genes of two Menderian factors S22A and S22B on rice chromosome inducing F1 pollen sterility in hybrids between O. sativa japonica-type cultivar Taichung 65 (T65) and a wild rice species O. glumaepatula. The causal gene of S22B in T65 encodes a protein containing DUF1668 and gametophytically expressed in the anthers, designated S22B_j. The O. glumaepatula allele S22B-g, allelic to S22B_j, possesses three non-synonymous substitutions and a 2-bp deletion, leading to a frameshifted translation at the S22B C-terminal region. Transcription level of S22B-j and/or S22B_g did not solely determine the fertility of pollen grains by genotypes at S22B Western blotting of S22B found that one major bands, type II, with approximately 39 kDa appeared only at the mature stage and were reduced on semi-sterile heterozygotes at S22B, implying that the type II bands may associated in hybrid sterility. In addition, causal genes of S22A in T65 were found to be S22A_j1 and S22A_j2 encoding DUF1668-containing proteins. The allele of a wild rice species O. meridionalis Ng at S22B, designated S22B_m, is a loss-of-function allele probably due to large deletion of the gene lacking DUF1668 domain and independently evolved from O. glumaepatula. Phylogenetic analysis of DUF1668 suggested that many gene duplications occurred before the divergence of current crops in Poaceae, and loss-of-function mutations of DUF1668-containing genes represent the candidate causal genetic events contributing to hybrid incompatibilities. The duplicated DUF1668-domain gene may provide genetic potential to induce HI by consequent mutations after divergence.